Experiences of Stalking in Same-Sex and Opposite-Sex Contexts - Sheridan, Lorraine; North, Adrian; Scott, A. (Springer, 2014)
Most stalking literature reports on male stalkers and female victims. This work examinesstalking experiences in 4 sex dyads: male stalker–female victim, female stalker–male victim,female–female dyads, and male–male dyads. Respondents were 872 self-defined victims ofstalking from the United Kingdom and the United States who completed an anonymoussurvey. The study variables covered the process of stalking, effects on victims and third parties,and victim responses to stalking. Approximately 10% of comparisons were significant,indicating that sex of victim and stalker is not a highly discriminative factor in stalkingcases. Female victims of male stalkers were most likely to suffer physical and psychologicalconsequences. Female victims reported more fear than males did, and most significantdifferences conformed to sex role stereotypes. Earlier work suggested stalker motivation andprior victim–stalker relationship as important variables in analyses of stalking, but these didnot prove significant in this work, perhaps because of sampling differences.